2021
DOI: 10.1590/1519-6984.224852
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity, antibacterial and inhibitory effect of intestinal disaccharidases of extracts obtained from Eugenia uniflora L. Seeds

Abstract: The use of medicinal plants for disease prevention, treatment and cure is an ancient practice used by humanity, and many plants species are used in bioprospecting research. In this context, its stands out Eugenia uniflora L., populary known as pitangueira and belongs to the Myrtaceae family, with a wide geographic distribution and native of Brazil. In view of the therapeutic qualities of the plant and the lack of the studies on its seeds, the present study had as objective to evaluate the phytochemical profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…The Ethanol extracts of species of red algae Callophyllis japonica (Kang et al, 2005) and Gracilaria tenuistipitata (Yang et al, 2012) shows antioxidant effects. Studies of an aqueous extract were examined with cell line which showed the recovery and enhanced of these cells from H 2 O 2 -induced DNA damage, counteracts cellular proliferation, and induced G2/M arrest that treatment of G. tenuistipitata (Yang et al, 2012;Lazzarotto-Figueiró et al, 2021). The discovery of novel fatty acids (FAs) with a wide range of new functions groups the study of fatty acid profiles as well as the presence of (FAs) in various lipid classes in microalgae is a new topic that promises to reveal a lot specially during their stationary phase in time producing and accumulate oil as carbon source, changes in fatty acid profiles under certain circumstances occur when microalgae try to acclimatize under unfavorable conditions (Wan Afifudeen et al, 2021).…”
Section: Isolation and Characterization Of Fatty Acids By Hplcmentioning
confidence: 99%
“…The Ethanol extracts of species of red algae Callophyllis japonica (Kang et al, 2005) and Gracilaria tenuistipitata (Yang et al, 2012) shows antioxidant effects. Studies of an aqueous extract were examined with cell line which showed the recovery and enhanced of these cells from H 2 O 2 -induced DNA damage, counteracts cellular proliferation, and induced G2/M arrest that treatment of G. tenuistipitata (Yang et al, 2012;Lazzarotto-Figueiró et al, 2021). The discovery of novel fatty acids (FAs) with a wide range of new functions groups the study of fatty acid profiles as well as the presence of (FAs) in various lipid classes in microalgae is a new topic that promises to reveal a lot specially during their stationary phase in time producing and accumulate oil as carbon source, changes in fatty acid profiles under certain circumstances occur when microalgae try to acclimatize under unfavorable conditions (Wan Afifudeen et al, 2021).…”
Section: Isolation and Characterization Of Fatty Acids By Hplcmentioning
confidence: 99%
“…It is the most reliable technique to determine substance antimicrobial properties. In Brazil, Lazzarotto-Figueiró et al (2021) reported a MIC value of 0.87 mg.mL -1 for the ethanolic extract of Eugenia uniflora L. leaves when testing against Staphylococcus aureus strains. They obtained higher MIC values when testing with Gramnegative bacilli (5 mg.mL -1 for Escherichia coli, 20 mg.mL -1 for Pseudomonas aeruginosa, and 10 mg.mL -1 for Salmonella typhymurium).…”
Section: Discussionmentioning
confidence: 99%
“…This genus is quite interesting from a chemical and pharmacological point of view and stands out for its therapeutic potential. Studies with species of this genus have shown promising results, such as antioxidant (Moresco et al, 2016) anti-inflammatory (Infante et al, 2016), antiviral (Sood et al, 2012), antibacterial (Simonetti at al., 2016;Lazzarotto-Figueiró et al, 2021) and hypoglycemic (Sharma et al, 2008).…”
Section: Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%
“…The assays were performed according to the broth microdilution methodology described by (Weber et al, 2014), with modifications. The E. involucrata plant extracts to obtain high value chemical products (Andrade et al, 2009;Oliveira et al, 2012;Lazzarotto-Figueiró et al, 2021).…”
Section: Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%